2020
DOI: 10.34172/jcs.2020.007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Health Literacy Counselling on Self-Care in Women after Mastectomy: a Randomized Clinical Trial

Abstract: Introduction:Breast cancer has a high prevalence, constituting a major cause of mortality in women around the world. Health literacy has a vital role in the self-care of chronic diseases such as cancer and is an essential element in the ability of each person to engage with health promotion. The aim of this study was to determine effect of health literacy counselling on selfcare in women after mastectomy. Methods: This study is a randomized, controlled, clinical trial carried out on 72 women with breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…In relation to the monthly income, more than two thirds of studied women had insufficient monthly income to their lives and their treatment according to their opinions, these findings go in the same line with Rastegar et al, (2020) in a study entitled -The Effect of Health Literacy Counseling on Self-Care in Women after Mastectomy" and reported that more than two thirds of studied women had not enough income. In the same context Mirzaei et al, (2019) in the study of -Supportive Care Needs in Females with Breast…”
Section: Resultssupporting
confidence: 82%
“…In relation to the monthly income, more than two thirds of studied women had insufficient monthly income to their lives and their treatment according to their opinions, these findings go in the same line with Rastegar et al, (2020) in a study entitled -The Effect of Health Literacy Counseling on Self-Care in Women after Mastectomy" and reported that more than two thirds of studied women had not enough income. In the same context Mirzaei et al, (2019) in the study of -Supportive Care Needs in Females with Breast…”
Section: Resultssupporting
confidence: 82%
“…literacy plays a vital role in self-care, with higher levels of health literacy associated with better blood pressure control. 8,9 Limited health literacy may impede self-care routines, resulting in hospital readmissions and challenges in comprehending health-related information. Improving health literacy has been shown to enhance self-care behavior in patients with chronic conditions such as diabetes.…”
Section: Discussionmentioning
confidence: 99%